Efeitos do campo magnético gerado por ímãs em cultura mista para biorremoção de cromo em efluentes contaminados - Dias, Roseli Mendonça (2018)
The environmentally appropriate release of industrial effluents containing heavy metals is subject to legislation that standardizes the contaminants concentrations before discharge into the receiving body. The treatment of effluent containing hexavalent chromium (Cr (VI)) by chemical precipitation is the most common, arousing interest in biological treatment since the former generates chemical residues at the end of the process. Chromium in its hexavalent form is more toxic than its trivalent form (Cr (III)), making chromium biorreduction one of the most used techniques in bioremediation of heavy metals. The use of a magnetic field in microorganisms called attention for the capacity of growth and biodegradation carried out by microorganisms. Thus, the present study aimed to quantify Cr (VI), total Cr, and total organic carbon (TOC) removal of synthetic effluent by applying a magnetic field at different frequencies (2.5, 3, 5 and 10 Hz) and only intensity of a magnetic field in mixed culture. Two bioreactors, one with neodymium magnets for generating a magnetic field and the other without magnets, were used in the evaluation of chromium removal and TOC during the 24 h of synthetic effluent recirculation. The configurations of the magnets were alternated in search of the best organization of magnets corresponding to the greater removal of Cr (VI). The initial Cr (VI) concentration was 100 mg L-1 for all tested bioreactor configurations. All configurations of bioreactors reached approximately 100% removal of Cr (VI), with the exception of the preliminary test, but with different process times and times of magnetic field application. The configurations of bioreactors that led to the largest removal of chromium and TOC were those with 40, 170, and 600 magnets. With 170 magnets, during the 4 h and 17 min of magnetic field application in the frequencies of 3, 5 and 10 Hz, which correspond to the flow rates of 3.93 cm3 s-1, 7.07 cm3 s-1, and 14.92 cm3 s-1, respectively, the magnetic field frequency of 5 Hz presented greater removal for Cr (VI) (99.91 ± 0.3%), total Cr (82.1 ± 1.5%), and TOC (34.2 ± 2.4%) when compared to frequencies of 3 and 10 Hz and without magnetic field application. For the bioreactor with 600 magnets, with flow rate 7.07 cm3 s-1 and magnetic field time of 14 h and 8 min, Cr (VI), total Cr, and TOC removal corresponded to 99.96 ± 1.4x10-3%, 61.6 ± 0.9%, and 40.8 ± 1.5%, respectively. For the bioreactor with 40 magnets, with a flow rate of 7.46 cm3 s-1 and magnetic field time of 7 h and 48 min, Cr (VI), total Cr, and TOC removal corresponded to 99.97 ± 0.01% , 74.2 ± 1.2%, and 25.1 ± 1.5%, respectively. When the number of magnets increased from 40 to 170, but with lower magnetic field intensity, total Cr removal was higher. However, when the magnets increased to 600 with greater magnetic field intensity, the total Cr removal decreased again. The desorption of chromium in synthetic effluent was also evaluated, showing all concentrations of Cr (VI) below the concentrations allowed to be released into the receiving body under current Brazilian CONAMA resolution 430/2011 (0.1 mg L-1). The rupture of the microbial cells showed that the amount of chromium retained in the cells by the experiment with a magnetic field was higher in comparison to the experiment without a magnetic field, indicating the possibility of recovery of this metal and to justify one of the mechanisms that increase the removal. The Infrared Spectroscopy analyzes corroborated the rupture tests, as it was found that Cr (III) was present in the biomass after treatment of the synthetic effluent. The morphology of the mixed culture analyzed by scanning electron microscopy showed no changes with the presence of chromium and a magnetic field. It was concluded therefore that the experiments in the bioreactor with magnetic field frequency of 5 Hz and only intensity of magnetic field presented the best Cr (VI), total Cr, and TOC removal compared to the bioreactor without a magnetic field for the evaluated time.